2006
DOI: 10.1294/jes.17.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laryngeal Hemiplegia of Thoroughbred Racehorses on Racing Performance and the Usefulness of Laryngoplasty Performed on Horses with Laryngeal Hemiplegia

Abstract: We evaluated the effect of laryngeal hemiplegia (LH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Defects such as lameness and RLN have been shown to affect the performance of the horse. A previous study comparing horses with and without RLN found that horses with RLN were less likely to return to racing after diagnosis, ran fewer races and were more likely to finish 4 s or more behind the winning horse compared to horses without RLN .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defects such as lameness and RLN have been shown to affect the performance of the horse. A previous study comparing horses with and without RLN found that horses with RLN were less likely to return to racing after diagnosis, ran fewer races and were more likely to finish 4 s or more behind the winning horse compared to horses without RLN .…”
Section: Discussionmentioning
confidence: 99%
“…Defects such as lameness and RLN have been shown to affect the performance of the horse. A previous study comparing horses with and without RLN found that horses with RLN were less likely to return to racing after diagnosis, ran fewer races and were more likely to finish 4 s or more behind the winning horse compared to horses without RLN . It is believed that defects such as tarsal plantar desmitis and metacarpal/metatarsal exostoses can be performance limiting, however, there is a lack of evidence to confirm this and the extent to which many other abnormalities affect racing performance has not yet been defined.…”
Section: Discussionmentioning
confidence: 99%